(untitled) (World Bulletin of Social Sciences, 2025)
The article examines the main similarities and differences between Russian and Uzbek languages in terms of grammar, vocabulary and phonetics. The study is aimed at identifying the difficulties that arise in those studying Russian or Uzbek as a foreign language, as well as at deepening intercultural communication between native speakers of both languages.